Design and analysis for a multifunctional rescue robot with four-bar wheel-legged structure. (February 2018) - Ning, Meng; Ma, Zefeng; Chen, Hanlong; Cao, Jun; Zhu, Changhong; Liu, Yifan; Wang, Yuefeng
Rescue robots can replace rescue workers in search and rescue missions in unknown environments and hence play an important role in disaster relief. To realize the advantages of high carrying capacity, easy control, and simple structure to adapt to a complex disaster scene, a novel wheel-legged rescue robot, integrated with rescue function modules, was designed for the present work. Three motion states were analyzed in detail. Mechanical properties were studied to provide basis for parameter optimization. The performance indices, which include mechanical properties, motion amplitudes and movement stability, were proposed, and the structural parameters were further analyzed and optimized based on these performance indices to make the overall performance of the robot achieve the best. Results show that the motion state of the wheel-legged rescue robot can perform real-time transformations and hence can be used in complex environments.